2017
DOI: 10.4274/balkanmedj.2016.0184
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Nipple Discharge: Value of Magnetic Resonance Imaging and Ultrasonography in Comparison with Ductoscopy

Abstract: Background:Pathologic nipple discharge, which is a common reason for referral to the breast imaging service, refers to spontaneous or bloody nipple discharge that arises from a single duct. The most common cause of nipple discharge is benign breast lesions, such as solitary intraductal papilloma and papillomatosis. Nevertheless, in rare cases, a malignant cause of nipple discharge can be found.Aims:To study the diagnostic value of ultrasonography, magnetic resonance imaging, and ductoscopy in patients with pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(49 reference statements)
0
10
1
3
Order By: Relevance
“…In our study, sensitivity and specificity of mammogram and ultrasound in diagnosing cases with pathologic nipple discharger was 71.4% and 54.2% respectively, while sensitivity and specificity of MRI was 100% and 83.3%. In a study done by Yılmaz R et al [1], the sensitivity of US was found higher in the identification of intraductal lesions than that in the literature [20,21]. This study revealed sensitivity and specificity for US as 75% and 66.7%, respectively.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In our study, sensitivity and specificity of mammogram and ultrasound in diagnosing cases with pathologic nipple discharger was 71.4% and 54.2% respectively, while sensitivity and specificity of MRI was 100% and 83.3%. In a study done by Yılmaz R et al [1], the sensitivity of US was found higher in the identification of intraductal lesions than that in the literature [20,21]. This study revealed sensitivity and specificity for US as 75% and 66.7%, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…This study revealed sensitivity and specificity for US as 75% and 66.7%, respectively. Ohlinger R et al [27] reported a sensitivity of 82.9%, higher than study done by Yılmaz R et al [1], but they calculated a specificity of 17.9%, which was lower than many studies. Ohlinger R et al [27] study was multicentered, so it is difficult to standardize diagnostic criteria; this high rate of sensitivity could in part be due to broad positive findings (e.g., cystic lesions and ductal ectasia).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations